Assessment of human expertise and movement kinematics in first-person shooter games - Donovan, Ian; Saul, Marcia A.; DeSimone, Kevin; Listman, Jennifer B.; Mackey, Wayne E.; Heeger, David J. (Frontiers in Human Neuroscience, 2022)
In contrast to traditional professional sports, there are few standardized metrics in professional esports (competitive multiplayer video games) for assessing a player’s skill and ability. We assessed the performance of professional-level players in Aim Lab ™, a first-person shooter training and assessment game, with two target-shooting tasks. These tasks differed primarily in target size: the task with large targets provided an incentive to be fast but imprecise and the task with large targets provided an incentive to be precise but slow. Each player's motor acuity was measured by characterizing the speed-accuracy trade-off in shot behavior: shot time (time interval between target appearance and the subsequent shot) and shot spatial error (distance from center of a target). We also characterized the fine-grained kinematics of players' mouse movements. Our findings demonstrate that: 1) movement kinematics depended on task demands; 2) individual differences in motor acuity were significantly correlated with kinematics; and 3) performance, combined across the two target sizes, was poorly characterized by Fitts Law. Our approach to measuring motor acuity has widespread applications not only in esports assessment and training, but also in basic (motor psychophysics) and clinical (gamified rehabilitation) research.